Do modern methods of post-mastectomy immediate breast reconstruction for breast cancer delay adjuvant therapy? - Syed, Abdul; Thomas, Harun; Smith, Simon; Ramakrishnan, Venkat (European Journal of Oncology and Environmental Health, 2019)
Background and aim of the work: Modern techniques of immediate breast reconstruction after mastectomies for breast cancer gives excellent cosmetic results and improve quality of life. However, it is perceived that immediate breast reconstruction may prolong recovery and can result in complications delaying adjuvant therapy. We aim to determine if there is such delay in the United Kingdom beyond the 31 days recommended by the National Institute for Health and Care Excellence. Methods: All patients who underwent mastectomy for breast cancer from January 2009 to August 2014 and received adjuvant treatment were categorised into three groups – mastectomy, implant / expander and flap. The primary end point was the time interval from the definitive surgical procedure to the start of adjuvant therapy. Results: Of the 192 patients (64 per group) analysed, mastectomy patients were significantly older, smokers and with higher nodal status (p<0.05). The groups were comparable with respect to other clinicopathological factors (p>0.05). Six patients from implant group and one patient from flap group started their adjuvant therapy within 31 days. The mean duration of adjuvant therapy was 63.2 days (33-202) in mastectomy group, 52.82 days (26-136) in implant group and 50.61days (29-89 days) after flap procedures (p=0.004). Conclusions: Our study shows a delay in initiating adjuvant therapy in keeping with published literature. The reasons could be multifactorial including delay in service provision. This delay is statistically significant in the mastectomy-alone patients, perhaps because they were older and smokers. Treatment pathways and multidisciplinary clinics will circumvent these concerns.